Reinterpreting Tasabbuh in the Context of the Boycott Movement Against Israeli-Linked Products: A Living Hadith Approach - Muh Khamdan; Ahmad Mujib; Abdullah Khusairi (International Journal of Religious and Interdisciplinary Studies, 2025)
This study addresses a pressing contemporary issue in Muslim communities: the ethical and jurisprudential dilemma surrounding the boycott of products linked to Israeli settlements in the occupied Palestinian territories. While such boycotts—endorsed by fatwas like MUI No. 83/2023—are framed as acts of economic solidarity, a critical concern arises when Muslims produce alternative goods that resemble boycotted items: does this constitute tasabbuh (imitation of non-Muslims), which is prohibited in several hadiths? The research aims to reinterpret the classical concept of tasabbuh within the framework of a “living hadith” approach, examining whether functional imitation—without intent to emulate beliefs or identity—violates Islamic norms. Using a qualitative methodology, the study combines textual analysis of primary hadith sources (including Sunan Abi Dawud, Sahih al-Bukhari, and Musnad Ahmad) with empirical observation of Muslim consumer behavior and fatwa discourse in Indonesia. Findings reveal that tasabbuh is primarily defined by intention (niyyah) and context, not mere formal similarity. When imitation serves a legitimate purpose—such as resisting injustice, ensuring economic self-reliance, or fulfilling communal welfare—it falls outside the scope of prohibited tasabbuh. This reinterpretation aligns with higher objectives of Islamic law (maqāṣid al-sharīʿah) and classical legal maxims (qawāʿid fiqhiyyah), particularly the principle that “matters are judged by their intentions.” The study’s novelty lies in bridging textual hermeneutics with real-world activism, offering a nuanced ethical framework for Muslim economic resistance. It is recommended that Islamic institutions and scholars issue clearer guidelines distinguishing between prohibited cultural imitation and permissible functional replication, especially in contexts of political and economic justice. Such clarity can empower Muslim communities to engage in ethical consumerism without compromising religious identity.